A Green Synthesis of Acetyl Eugenol by Sonochemical Method and Potential as Anti-Inflammatory In-Vitro - Rahmawati Salsa Dinurrosifa; Erwin Indriyanti (JKPK (Jurnal Kimia dan Pendidikan Kimia), 2022)
Clove oil is an essential oil from the clove plant (Syzygium aromaticum) containing eugenol compounds. One of the properties of eugenol is as an anti-inflammatory with a mechanism of inhibition of prostaglandin synthesis and neutrophil chemotaxis. Several derivatives of eugenol have active compounds that have been developed into new drug compounds as anti-inflammatory such as acetyl eugenol (4-allyl-2-methoxyphenyl acetate). This study aims to determine the % yield of acetyl eugenol produced from synthesis using ultrasonic 0.0323 mol of eugenol added to Erlenmeyer, and 0.25 mol of 10% sodium hydroxide was added. The mixture was put in a sonicator for 15 minutes and heated at 600C. Then, 0.0974 mol acetic anhydride was reacted with DCC, added to the mix and sonicated with time variations (60, 80, and 100 minutes). The chemical structure was elucidated using FTIR, ATR, and GC-MS. The synthesized % yield is 32.75%. Based on the interpretation data from FTIR, 3405 cm-1 is an O-H group (free phenol), 1405 cm-1 is an alkene group (C=C) aliphatic, and 1560 cm-1 is an aromatic compound with the presence of a C=C aromatic bond. The presence of the (C-O) ether group is indicated in the wave number at 1301 cm-1. The C=O ester bond in the ester group is shown at 1700 cm-1. GC-MS shows that the synthesized compound has a molecular ion with m/z = 206. According to the molecular weight of acetyl eugenol of 206 g/mol, it can be concluded that acetyl eugenol was successfully synthesized. The most stable ionic fragment, 37, has a molecular weight of m/z = 164. The activities of anti-inflammatory, acetyl eugenol compounds at 400 concentration ppm get % inhibition of 32.20%.